The Signaling Role of Charitable Contributions by Businesses: A Tax Policy Perspective - Tomer Blumkin; Yoram Margaliioth; Efraim Sadka; Adi Sharoni (Center for Economic Studies and ifo Institute (CESifo), 2016)
Empirical evidence suggests that charitable contributions to public goods may be driven not only by the familiar warm-glow of giving motive but also as a means for businesses to signal high product quality. Building on this finding, we present an analytical framework that characterizes the optimal government policy, assuming that the government may either directly provide the public good or subsidize its private provision. We show that in the optimal solution the government should subsidize the private provision of the public good and refrain from direct provision. We further demonstrate that the optimal degree of subsidization should decrease with the extent to which the signal is informative, and may even turn into a tax when the signal is sufficiently strong. Finally, we compare the current practice in the US, a charitable contribution deduction provided by Section 170 of the US Tax Code, with the optimal design suggested by our normative analysis and offer changes that would bring the Section closer to the social optimum.
Keywords: H20; H40; K30; 330; public goods; Pigouvian taxation; warm glow; signaling